Non-invasive prenatal testing for the detection of trisomy 13, 18, and 21 and sex chromosome aneuploidies in 68,763 cases - Zhang, Yanchun; Xu, Hongyan; Zhang, Wen; Liu, Kaibo (Frontiers in Genetics, 2022)
Objectives: Noninvasive prenatal testing (NIPT) has been widely used in recent years. We explored the feasibility of NIPT for analysis of common fetal aneuploidies among pregnancies in Beijing. Methods: A total of 68,763 maternal blood samples were collected from January 2020 to December 2020 at the Beijing prenatal diagnosis agency. Cases with positive screening results by NIPT detection were validated using prenatal diagnosis. Results: Positive NIPT occurred in 920 cases; 755 cases with positive NIPT results were shown to be truly positive by chromosome karyotyping analysis. Among the 68,763 pregnant women, the prenatal diagnosis rate was 82.07%. Of the 920 cases, there were 164 cases of trisomy 21 (T21), 70 of trisomy 18 (T18), 38 of trisomy 13 (T13), 360 with sex chromosome abnormalities (SCAs) and 288 with other chromosome abnormalities. Rates of trisomy 21, 18, 13 and SCA positivity were 0.24%, 0.10%, 0.06% and 0.52%, respectively. Sensitivity and specificity were 98.17% and 99.92% for T21, 96.15% and 99.93% for T18, and 100% and 99.95% for T13, respectively. Positive predictive values (PPVs) of trisomy 21\18\13 and SCAs were 65.24%, 35.71%, 18.42% and 31.39%, respectively. The highest rate of NIPT detection indication was for nuchal translucency (NT) thickening (2.03%) for T21; ultrasound structural abnormalities were observed for T18 and T13. The highest PPV (100%) of NIPT detection indication was for ultrasound structural abnormalities and ultrasound soft marker abnormalities for T21 and ultrasound structural abnormalities and NT thickening for T18 and T13. The PPVs of different clinical indications for T21 (p=0.002), T13 (p=0.04) and SACs (p=0.02) were statistically significant. Conclusions: The high specificity, efficiency and safety (noninvasiveness) of NIPT can effectively avoid birth defects. We should encourage pregnant women with NIPT-positive results to undergo prenatal diagnosis to distinguish whether the fetus has chromosomal abnormalities to avoid bringing financial burden to the family.